MAKING OF SIMPLE LED SPECTROPHOTOMETER EXPERIMENT KIT FOR ANALYSIS OF IRON METAL IONS IN WATER - Dudi Fatul Jawad; Yulia Sukmawardani; Ida Farida (UIN Sunan Gunung Djati Bandung, 2021)
This study aimed to describe the appearance of the KIT making, how to use the KIT, and the validation test results for the making of a simple LED spectrophotometer for the analysis of iron metal ions in water. The method used was Design Based Research. This method refers to the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. However, researchers only used the model until the development stage, starting from collecting references (journals), making concept analysis, concept maps, flowcharts, and storyboards, and the validation test of the three validators. The results from the KIT development stage could be carried out well, resulting in a valid product with indicators that include an attractive display of the KIT, easy to use, low cost, and KIT made of safe materials. The results of the validation test obtained an average value of 0.83, greater than the critical value of 0.30. This shows that the simple LED spectrophotmeter experiment KIT is valid for a feasibility test. In learning, the use of KIT refers to the spectrophotometric material which is based on the Lambert-Beer law and the analysis results that will be produced are in the form of a comparison curve of normal intensity with a wavelength in units of nanometers (nm).